(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
Forensic Science means the application of science to those criminal and civil laws that are enforced by the police agencies in a criminal justice system .Forensic Science plays a vital role in the criminal justice system by providing scientifically based information through the analysis of physical evidence. It involves the use of multiple disciplines such as physics, chemistry, biology, computer science and engineering for evidence analysis. In this paper I would like to analysis how far the forensic techniques are effective in the crime scene investigation and its importance in the present society.